2021
DOI: 10.1371/journal.pone.0245686
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on tuberculosis and utilization of DOTS service by tuberculosis patients in Lalitpur District, Nepal

Abstract: Background Tuberculosis is one of the major infectious diseases and is both complex and serious. It is spread from person to person through the air, causing a public health burden, especially in low- and middle-income countries. This study aims to assess the knowledge on tuberculosis and the utilization of Directly-Observed Therapy, Short Course (DOTS) service from the public DOTS centers in Lalitpur district of Nepal. Method A structured questionnaire was used to collect data from 23 DOTS centers in Lalitpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
3
0
1
Order By: Relevance
“…In 2020, the COVID-19 pandemic dislodged TB from the top infectious disease cause of mortality globally [1]. In Nepal, in 2018, about 69,000 people were living with TB, but only 32,474 cases were reported in the National Tuberculosis Program [8]. While most of the cases of TB are pulmonary; extrapulmonary TB (EPTB) accounts for above one-fifth of the global burden of the disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, the COVID-19 pandemic dislodged TB from the top infectious disease cause of mortality globally [1]. In Nepal, in 2018, about 69,000 people were living with TB, but only 32,474 cases were reported in the National Tuberculosis Program [8]. While most of the cases of TB are pulmonary; extrapulmonary TB (EPTB) accounts for above one-fifth of the global burden of the disease [9].…”
Section: Discussionmentioning
confidence: 99%
“…The Knowledge on tuberculosis and utilization of DOTS service by tuberculosis patients in Lalitpur District, Nepal further supports the fact that approximately one quarter of the patients did not have adequate knowledge of tuberculosis and were not utilizing the DOTS service efficiently [11] A nine city longitudinal study from India assessing the knowledge about tuberculosis and infection prevention behaviour had concluded that social proximity between health worker and patients predicted greater knowledge and adherence to infection prevention behaviors but unfortunately, data suggests that the latter rate remains undesirably low [12].…”
Section: Discussionmentioning
confidence: 68%
“…Few numbers of patients took treatment themselves without observation. Nearly a quarter of TB patients did not take Directly Observed Treatment (DOT) of from the designated treatment centre in Nepal [25]. None of the patients received their medication from the Community DOT providers, which is a crucial and interesting finding from this study.…”
Section: Discussionmentioning
confidence: 82%